2015
DOI: 10.1002/stem.1895
|View full text |Cite
|
Sign up to set email alerts
|

Concise Reviews: Can Mesenchymal Stromal Cells Differentiate into Corneal Cells? A Systematic Review of Published Data

Abstract: The majority of stem cell therapies for corneal repair are based upon the use of progenitor cells isolated from corneal tissue, but a growing body of literature suggests a role for mesenchymal stromal cells (MSC) isolated from noncorneal tissues. While the mechanism of MSC action seems likely to involve their immuno-modulatory properties, claims have emerged of MSC transdifferentiation into corneal cells. Substantial differences in methodology and experimental outcomes, however, have prompted us to perform a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 43 publications
(104 reference statements)
4
44
0
4
Order By: Relevance
“…These findings are in agreement with Harkin et al, (2015) who reported that BM-MSCs enhanced epithelial healing. This occured through various ways by which the MSCs reconstructed the corneal injuries after corneal alkali burn by growth factors and cytokines secretions which regulated cell proliferation and signaling.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with Harkin et al, (2015) who reported that BM-MSCs enhanced epithelial healing. This occured through various ways by which the MSCs reconstructed the corneal injuries after corneal alkali burn by growth factors and cytokines secretions which regulated cell proliferation and signaling.…”
Section: Discussionsupporting
confidence: 93%
“…MSCs derived from bone marrow, adipose tissue, umbilical cord or dental pulp [211,212] were demonstrated to acquire both epithelial cell-like [213,214] and keratocyte-like characteristics [215][216][217] (see [195] for a systematic review). The therapeutic use of bone-marrow or adipose tissue-derived MSCs, by local injection or topical application in animal models of chemical burns, was shown to improve corneal healing and reduce corneal inflammation and neovascularization [218][219][220][221].…”
Section: Mdpimentioning
confidence: 99%
“…Innym białkiem obecnym w LESC jest cytokeratyna 19 (CK19). Również w tym wypadku nie występuje ona wyłącznie w rogówce, dlatego podobnie jak p63 nie może być markerem specyficznym narządowo [13,23,26]. Markerem zwią-zanym z komórkami progenitorowymi nabłonka rogówki jest białko transporterowe z nadrodziny ABC typu G2 (ABCG2), uniwersalny marker komórek macierzystych [27,28].…”
Section: Identyfikacja Komórek Macierzystych Rąbka Rogówkiunclassified
“…Białka α9-, α6-, β1-integryny [23], cytokeratyna 15 (CK15), cytokeratyna 14 (CK14) [13] oraz receptor EGFR również używane są jako markery komórek progenitorowych rąbka rogów-ki [16]. Potwierdzono natomiast, że komórki warstwy epitelialnej rogówki wykazują ekspresję cytokeratyny 3 (CK3) oraz cytokeratyny 12 (CK12) [26,27,28,29]. Nie stwierdzono obecności tych białek w komórkach epitelialnych pochodzących z rąbka rogówki [23,30,31].…”
Section: Identyfikacja Komórek Macierzystych Rąbka Rogówkiunclassified